2021
DOI: 10.1002/mabi.202100005
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanomedicine in Cancer Therapy: Targeted Delivery and Cellular Uptake

Abstract: Nanomedicine has gained much attention for the management and treatment of cancers due to the distinctive physicochemical properties of the drug‐loaded particles. Chitosan's cationic nature is attractive for the development of such particles for drug delivery, transfection, and controlled release. The particle properties can be improved by modification of the polymer or the particle themselves. The physicochemical properties of chitosan particles are analyzed in 126 recent studies, which allows to highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 171 publications
(237 reference statements)
1
24
0
Order By: Relevance
“…The crystal structures of the CS, Zn-BTC, and Zn-BTC@CS nanocomposite were measured by XRD (Rigaku, Tokyo, Japan) using Cu Kα radiation (λ = 0.154 nm) at 40 kV and 30 mA with a 2θ range from 5° to 80°. The d values of the mean diameter of the samples were calculated according to the Scherrer equation [ 35 ]: d = k λ /(βcosθ), where d is crystallite size, k is a constant applied as 0.89, λ is the X-ray wavelength, β is the full width at half-maximum, and θ is the Bragg angle.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structures of the CS, Zn-BTC, and Zn-BTC@CS nanocomposite were measured by XRD (Rigaku, Tokyo, Japan) using Cu Kα radiation (λ = 0.154 nm) at 40 kV and 30 mA with a 2θ range from 5° to 80°. The d values of the mean diameter of the samples were calculated according to the Scherrer equation [ 35 ]: d = k λ /(βcosθ), where d is crystallite size, k is a constant applied as 0.89, λ is the X-ray wavelength, β is the full width at half-maximum, and θ is the Bragg angle.…”
Section: Methodsmentioning
confidence: 99%
“…The molecule has a straight-chain structure, and weighs between 10 and 1,000 kDa (Kou et al, 2021). Chitosan is widely utilized for antibacterial purposes (Muxika et al, 2017), drug release (Hudson and Margaritis, 2014), target therapy (Mushtaq et al, 2021;Narmani and Jafari, 2021), and drug delivery in stomatology (Ahsan et al, 2018). Studies have shown that it effectively inhibits the biofilm formation and the acid production capacity of Streptococcus mutans, the main causal agent of dental caries (Kawakita et al, 2019).…”
Section: Chitosanmentioning
confidence: 99%
“…Nanomedicine is a newly emerging field that has gained significant attention worldwide. The technology in this field allows for the deeper exploration of cellular compartments, and may help to combat several diseases, including cancer ( Mushtaq, 2021 ). The development of therapeutic nanomedicine-delivery systems represents a challenge for research groups worldwide ( Bamburowicz-Klimkowska et al, 2019 , Bastiancich, 2019 ), and there is high demand for a system that combines active functional drugs with an efficient delivery vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most prominent natural polysaccharides and is widely used in nano-drug delivery systems, due to its biocompatibility and biodegradability ( Jhaveri, 2021 , Narmani and Jafari, 2021 ). Chitosan has several properties that make it an efficient nanocarrier, including high stability levels in serum, low immunogenicity, lengthy circulation time, biocompatibility and high bioavailability ( Mushtaq, 2021 , Narmani and Jafari, 2021 , Pejin, 2014 ).…”
Section: Introductionmentioning
confidence: 99%